Resilience analysis of urban settlements against the flood with emphasis on Social and economic indicators Case study : ( Gorgan city) - shamsi sadat mir asadollahi; sadraldin motavali; gholam reza janbaz ghobadi (تحقیقات کاربردی علوم جغرافیایی)
Natural disasters are a set of harmful events that are natural origin that sometimes human factors are also effective in exacerbating. In the same vein strengthening the social and economic component and after that resiliency can play an important and effective role in reducing flood damage. This research is applied in terms of purpose and descriptive –analytical and field nature. Survey method and data gathering tool were closed questionnaires, the analysis method is based on correlation and regression test. The statistical population includes citizens living around the river and flood areas that 383 people selected as sample and the questionnaire was distributed by cluster sampling among respondents, according to research finding , the average social resilience 1/60 , average economic aberration ( the amount of damage ) 4/53 ,average capacity with ability to compensate 8/69 , eventually average return to appropriate condition 4/67 .in the test section, hypotheses are determined according to the result of the regression test and correlation which has a significant relationship between urban and urban spatial and social dimensions. Strengthen local organs and organizations in a decentralized state  , one of the important ways to increase the social participation of citizens of Gorgan during the crisis.by providing people's participation and strengthening the people's economic ability when natural hazards occur including flood, the initiative of the people is strengthened and the scope for reducing the damage caused by the flood is reduced . people are faced with real and tangible issues with the executive and so on their gap crisis management and conflicts of interest will diminish.